Corrosion inhibition of mild steel in acidic media using new oxo-pyrimidine derivatives: Experimental and theoretical insights - Ferigita, Khaled Saad Miled; Saracoglu, Murat; AlFalah, Mothana Ghazi Kadhim; Yilmazer, Mehmet Izzettin; Kokbudak, Zülbiye; Kaya, Savaş; Kandemirli, Fatma (Elsevier BV, 2023)
Interesting results have been found for new compounds derived from oxo-pyrimidine to protect ofmild steel (MS) in 1 M hydrochloric acid. These the compounds are 1-(5-(4-Methoxy-benzoyl)-4-(4-methoxy-phenyl)-2-oxo-2H-pyrimidin-1-yl]-(4-methoxy-phenyl)-urea (MMOM) and 1-(5-(4-methoxy-benzoyl)-4-(4-methoxy-phenyl)-2-oxo-2H-pyrimidin-1-yl)-3-(4-methlyphenyl)-thiourea (MMOPM). In this study, the impact of immersion time on inhibitor effectiveness wasalso investigated. Both substances function as mixed-type inhibitors, according to theelectrochemical data. At 5×10-4 M and a 72-hour immersion duration, MMOM is more effectivethan MMOPM (98.42% vs. 94.49%). The Langmuir isotherm system provided the best match forboth compounds, with chemisorption as the kind of adsorption. According to the findings ofsurface characterisation, both chemicals may be adsorbed on mild steel surfaces to reducecorrosion. Inhibitor simulations using density functional theory revealed that the protonated stateis more reactive than the neutral state and coincides with experimental findings. The outcomesdemonstrated that both compounds may be utilized as new mild steel corrosion inhibitors in harshconditions and long-term immersion. The theoretical study, based on quantum chemicalcalculations of the compounds, performed by the DFT/BP86 method with a 6-311G(d,p) basis setby using Gaussian 09, Revision A.02 program, were also included to support experimental results.The various quantum chemical parameters such as EHOMO, ELUMO, chemical hardness and chemicalsoftness, electronegativity of the investigated molecules were calculated, and their inhibitionefficiency were discussed. The outcomes demonstrated that both compounds may be utilized asnew mild steel corrosion inhibitors in harsh conditions and long-term immersion